Patient Satisfaction Of Pregnant Mothers With Antenatal Care Services At Puskesmas Petisah Medan - Selli M Pasaribu; Dame Meldaria Sipahutar; Sarma Dewi Kemala (International Archives of Medical Sciences and Public Health, 2022)
Patient satisfaction is the degree of perfection of health services in accordance with professional standards and service standards by using the potential resources available at the hospital or health center in a reasonable, efficient, and effective manner and provided safely and satisfactorily according to norms, ethics, law, and socio-culture. taking into account the limitations and capabilities of the government, as well as the consumer society. The purpose of this study was to identify the level of patient satisfaction with antenatal care services at the Petisah Health Center Medan. The research methodology used is descriptive research. The number of samples used as many as 34 people. The sampling technique used is total sampling technique. This research was conducted in the PWS-KIA room at the Petisah Health Center, Medan. With the results that four patients (11.8%) stated that they were very satisfied, 26 patients (76.4%) said they were satisfied and four patients (11.8%) said they were not satisfied, the majority of patients said they were satisfied with the antenatal care services. At the Petisah Health Center Medan, it is recommended that the Medan Petisah Health Center can maintain good services and improve the quality of standardized services for antenatal care patients so that the satisfaction expected by patients is realized in providing antenatal care services according to the 10T standard.